2008
DOI: 10.1007/s11258-008-9457-3
|View full text |Cite
|
Sign up to set email alerts
|

Root plasticity of native and invasive Great Basin species in response to soil nitrogen heterogeneity

Abstract: Soil nutrients are heterogeneously distributed in natural systems. While many species respond to this heterogeneity through root system plasticity, little is known about how the magnitude of these responses may vary between native and invasive species. We quantified root morphological and physiological plasticity of co-occurring native and invasive Great Basin species in response to soil nitrogen heterogeneity and determined if trade-offs exist between these foraging responses and species relative growth rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 44 publications
(57 reference statements)
0
40
1
Order By: Relevance
“…However, the 15 N uptake rate of S. alterniflora was lower than that of P. australis in our study, which contrasts with Blicker et al [16], who found that invasive species exhibited greater 15 N uptake rates than native species. This seeming disadvantage of S. alterniflora in our study might be offset by its greater allocation of biomass to the root system and its greater nitrogen use efficiency.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the 15 N uptake rate of S. alterniflora was lower than that of P. australis in our study, which contrasts with Blicker et al [16], who found that invasive species exhibited greater 15 N uptake rates than native species. This seeming disadvantage of S. alterniflora in our study might be offset by its greater allocation of biomass to the root system and its greater nitrogen use efficiency.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the potential role of roots in the success of plant invasions has been largely overlooked. Plant roots play a vital role in the uptake of nutrients and other resources, and root plasticity is one of the central mechanisms for plant resource exploitation and acquisition [14].Resource capture capacity of roots varies substantially among species [15][16][17], yet few studies have compared the differences in resource uptake and physiological plasticity of roots responding to different resource levels between invasive and native plants [16,18]. In China, the invasive C 4 grass species smooth cordgrass (Spartina alterniflora) is receiving increasing attention.…”
mentioning
confidence: 99%
“…These plastic responses by the root system have been proposed as the major mechanism employed by the root system to allow plants to cope with the heterogeneous supply of nutrients in soil1. Variations in both root biomass and N uptake rate per unit root biomass are important in contributing to the variations in the abilities of species to capture N from ephemeral patches8. Field studies have shown that plant roots respond most strongly to N given in pulses and least strongly to a continuous nutrient supply9.…”
mentioning
confidence: 99%
“…Field studies have shown that plant roots respond most strongly to N given in pulses and least strongly to a continuous nutrient supply9. Furthermore, there was a positive relationship between N uptake rate, relative growth rate, and root system biomass8. In addition to the plastic responses of plant roots, there have been reports that soil N heterogeneity influences seedling recruitment10, vegetation succession11, plant species coexistence and competition12, and invasion of non-native plants into natural ecosystems13.…”
mentioning
confidence: 99%
“…Downy brome displays a superior ability to extract soil resources, both generally ( James et al, 2009) and specifically in the cooler months, making it competitive against natives that do not initiate root growth until spring (Harris, 1967;Kulmatiski et al, 2006a). Downy brome is less dependent on soil mycorrhizal associations than native perennial grasses for nutrient extraction, possibly because of its high root-surface area (Owen et al, 2013).…”
Section: Downy Brome Invasion and Its Impactsmentioning
confidence: 99%